Impact of services trade on India's economic growth and current account balance: Evidence from post-reform period - Mini P. Thomas (FIW - Research Centre International Economics, 2016)
Economic Growth and External Stabilisation (defined in terms of Current Account Balance as a percentage of GDP) is a top priority for policy-makers, while laying out the macroeconomic framework for Indian economy. Government of India had targeted for an average GDP growth rate of 9 percent and a Current Account Deficit (CAD) below 2.5 percent of GDP during the five-year period from 2012-2017. However, the actual CAD of Indian economy widened to 4.2% of GDP in 2011-12, and further reached a historic high CAD of 4.7 percent of GDP in 2012-13. Given such a scenario, this paper aims to estimate the impact of services trade on India's Economic Growth and Current Account Balance, during the post-reform period from 1990-91 to 2011-12. Facilitated by economic globalisation, domestic liberalization, and technological advances which resulted in increasing international fragmentation of the production process, India's services trade began growing rapidly post 1991. With the help of Thirlwall's Balance of Payments Constrained Growth Model and ARDL approach to cointegration, this study estimates and establishes the crucial role of services trade in achieving the policy objectives of economic growth and external stabilisation simultaneously for Indian economy. This study also examines the impact of services exports on India's economic growth, by comparing the latest officially published input-output table of India for 2007-08, with that of 1993-94. Among the major services in India's export basket, construction, transport and business services are found to exhibit strongest backward linkages, and hence can act as engines of export-led growth. Role of services imports in India's export-led growth and the import content going into production of India's services exports is analysed using the TIVA database for 1995 and 2008, which have implications for India's external stabilisation. Foreign value added content in India's services exports is found to be highest in case of business services, transport services and telecommunications.
Keywords: F14; F32; F43; C67; 330; services trade; Current Account Deficit; economic growth; backward linkages; trade in value added